Recobrimento e condicionamento fisiológico de sementes de cebola e cenoura - Holbig, Letícia dos Santos (2007)
The objective of the study was to evaluate the physiological performance of onion seed after hydroconditioning and coated with polymer and fungicide. Onion seeds cv. Ball early-Hortec ®, Bagé / RS; have been used and subject to hydroconditioning physiological or hydroconditioning samples in 5.0 g of seed pads between two sheets of paper Germitest, with 2.5 times the dry weight of the paper, for 24 hours at 25 ° C. After hydroconditioning made to the drying of the seed in greenhouses with circulation of air forced to ± 35 ° C for 20 hours, until they reach the initial humidity of 7%. Soon after was the coated with polymer-Colorseed Rigran ® in the dose of 50mL.kg-1 and the fungicide Captan ® in the dose of 0.002 g.kg-1. The treatments were to: 1-witness, 2-seed+fungicide, 3 seed+polymer, 4-seed+fungicide +polymer, 5-seed hydroconditioned, 6-seed hidrocondicionada + fungicide, 7-seed hidrocondicionada + polymer, 8 seed+fungicidehidrocondicionada+ polymer. The statistical approach was used 2X4 factorial, with 4 repetitions and averages were compared by Duncan test of the level of significance of 5%. Results showed that the seeds of onion hydroconditioning promoted germination, speed emergency and the percentage of seedlings emerged. Seeds hydroconditioned led seedlings greater and greater accumulation of biomass. Seeds of onion hydroconditioned and covered with polymer-Colorseed Rigran® in the dose of 50mL. Kg-1 and fungicide Captan® at the dose of 0.2%, expressed force that better seeds not conditional.